ANALISIS EFEKTIVITAS PEMERINTAH DESA DALAM PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDES) DI DESA SUMAMPIR KECAMATAN REMBANG KABUPATEN PURBALINGGA - Afri Damayanti; Warsito Kawedar (Diponegoro Journal of Accounting, 2025)
The purpose of the study is to analyze the effectiveness of the village government in managing the village revenue and expenditure budget. This study is a qualitative study with a descriptive approach using data collection methods through interviews and documentation. Then the data obtained is analyzed using data analysis techniques through several stage as follows: categorization, rasionalization of relations, data presentation, drawing conclusions. This study was conducted in Sumampir Village, Rembang District, Purbalingga Regency. Based on the data obtained in the field, the author can conclude that the management of the village revenue and expenditure budget carried out by the village government has effective and meffective results. In the management of the village revenue and expenditure budget in the field of village development and the field of emergency and urgent disaster management. The management of the village revenue and expenditure budget in the field of community development and community empowerment has been effective.